Employer's Satisfaction on Accounting Service Performance: A Case of Public University Internship Program. (15th June 2016) - Sawani, Yussri; Abdillah, Azlin; Rahmat, Mariam; Noyem, Josephine Avelind; Sirat, Zahrah
Abstract: Internship programs have become important learning tools in higher education. For the accounting discipline, internship helps bridge the gap between technical inputs in class and actual application in real time transaction. The Accounting Internship program develops students' accounting experience by enabling them to learn the ropes from more experienced professionals. At the end of the program, students are expected to grab relevant experience to help them decide the area that suits them best. Accounting students typically specialize in either audit or tax. Many accounting firms have their standard internship programs that help students determine which aspect of accounting is more suitable for them. In many cases, the internship programs are normally conducted towards the end of the period of study to enable students to apply their comprehensive accounting knowledge in the real world. It is expected that at this level students are equipped with necessary skills in accounting. This study preliminarily aims to identify the employer's satisfaction level on student's performance that include personality traits as well and their cognitive accounting skills and knowledge. The study employed the questionnaire survey distributed to both Big 4 and non-Big 4 accounting firms. Findings of the study revealed that most employers were satisfied with the trainee's performance in relation to job competency responsibility and compliance with working requirements. However, it was found that trainees faced problems in communicating their ideas and preparing technical reports. This study provided preliminary evidence that the trainees were not equipped with the ability to effectively communicate ideas and prepare technical accounting reports. Implications and future research directions of this study were discussed.